Cystic fibrosis research topics featured at the 14th ECFS Basic Science Conference: chairman's summary - Mall, Marcus A. (Journal of cystic fibrosis, 2018)
In recent years, tremendous progress has been made in the development of novel drugs targeting the basic defect in patients with cystic fibrosis (CF). This breakthrough is based on a solid foundation of knowledge on CFTR's function in health and how mutations in CFTR cause CF multi-organ disease. This knowledge has been collected and continuously expanded by an active and persistent CF research community and has paved the way for precision medicine for CF. Since 2004, the European Cystic Fibrosis Society (ECFS) has held an annual Basic Science Conference that has evolved as an international forum for interdisciplinary discussion of hot topics and unsolved questions related to CF research. This Special Issue reviews CF research topics featured at the 14th ECFS Basic Science Conference and provides an up-to-date overview of recent progress in our understanding of CFTR structure and function, disease mechanisms implicated in airway mucus plugging, inflammation and abnormal host-pathogen interactions, and advancements with enhanced cell and animal model systems and breakthrough therapies directed at mutant CFTR or alternative targets. In addition, this Special Issue also identifies a number of fundamental questions and hurdles that still have to be overcome to realize the full potential of precision medicine and develop transformative therapies for all patients with CF.